Ana Corbalán and Ellen Mayock. Toward a Multicultural Configuration of Spain: Local Cities, Global Spaces. Madison: Fairleigh Dickinson UP, 2015. vii–xix + 211 pp. - Jennifer Brady (Studies in 20th & 21st Century Literature, 2016)
Review of Ana Corbalán and Ellen Mayock. Toward a Multicultural Configuration of Spain: Local Cities, Global Spaces. Madison: Fairleigh Dickinson UP, 2015. vii–xix + 211 pp.
Keywords: multiculturalism; Spain